Eksistensi Variasi Akad Kerjasama Penggarapan Sawah di Kabupaten Hulu Sungai Tengah - Khairanor; Anwar Hafidzi; M. Hanafiah (Indonesian Journal of Islamic Jurisprudence, Economic and Legal Theory, 2023)
ABSTRACT Collaboration in cultivating rice fields in Hulu Sungai Tengah Regency carried out by the community (rice field owners and farmers) has three types of contracts that can be options for application, although they are different but have the same goal, the contracts are divided into three, namely bakarun, basewa and basanda. The visible difference is in the way the results are distributed, the bakarun is divided by percentage, namely the results are divided by 3 first, then the rice field owner gets 1/3 and the farmer gets 2/3. As for the basewa, the distribution of results for the rice field owner has been determined at the beginning of the agreement as a fee for renting the rice field, while the basanda contract has the same distribution as the basewa system, but in the basanda contract there is a previous debts and receivables agreement. The author is interested in discussing this because the people of Upper Banjar have very natural/natural habits in carrying out cultural customs which are wrapped in a socio-economic dimension, the social is cooperation while the economic is agriculture. This encourages the author to elevate this habit into the realm of Sharia Economic Law. This research is to find out a description of the cooperation agreement for cultivating rice fields using the bakun, sewa and sanda system, which is then reviewed in basic terms from the perspective of Sharia Economic Law. Keywords: Hulu Sungai Tengah, Cooperation Agreement, Existence ABSTRAK Kerjasama penggarapan sawah di Kabupaten Hulu Sungai Tengah yang dilakukan masyarakat (para pemilik sawah dan petani) ada tiga macam akad yang dapat menjadi opsi untuk di aplikasikan, meskipun berbeda namun satu tujuan yang sama, akad itu terbagi tiga, yakni bakarun, basewa dan basanda. Perbedaan yang nampak adalah pada cara pembagian hasilnya, bakarun dibagi dengan cara persentase yakni hasilnya dibagi 3 terlebih dahulu kemudian pemilik sawah dapat 1/3 dan petani mendapat 2/3. Adapun basewa pembagian hasil untuk pemilik sawah sudah ditentukan diawal kesepakan sebagai biaya sewa sawah, sedangkan akad basanda pembagiannya sama dengan sistem basewa namun terhadap akad basanda terdapat akad utang-piutang sebelumnya. Penulis tertarik membahas hal ini karena pada masyarakat Banjar bagian Hulu tersebut memiliki kebiasaan yang sangat natural/alami dalam melangsungkan adat budaya yang dibungkus dengan dimensi sosial ekonomi, sosialnya adalah kerjasama sedangkan ekonominya adalah pertanian. Hal ini mendorong penulis untuk mengangkat kebiasaan tersebut ke dalam ranah Hukum Ekonomi Syariah. Penelitian ini untuk mengetahui deskripsi tentang akad kerjasama penggarapan sawah dengan sistem bakarun, sewa dan sanda, yang kemudian ditinjau secara dasar dengan perspektif Hukum Ekonomi Syariah. Kata Kunci: Hulu Sungai Tengah, Akad Kerjasama, Eksistensi